2015
DOI: 10.1093/icesjms/fsv123
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of deep-sea fisheries on benthic communities: a review

Abstract: Deep-sea fisheries operate globally throughout the world's oceans, chiefly targeting stocks on the upper and mid-continental slope and offshore seamounts. Major commercial fisheries occur, or have occurred, for species such as orange roughy, oreos, cardinalfish, grenadiers and alfonsino. Few deep fisheries have, however, been sustainable, with most deep-sea stocks having undergone rapid and substantial declines. Fishing in the deep sea not only harvests target species but can also cause unintended environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
301
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(309 citation statements)
references
References 137 publications
5
301
2
1
Order By: Relevance
“…Trawl gear can damage CWC communities by reducing or changing coral abundances, diversity and community or the removal of structuring species (reviewed by Clark et al, 2016), as shown for coral reefs of the NE Atlantic (Hall-Spencer et al, 2002) and Solenosmilia thickets on Australian seamounts (Althaus et al, 2009). In addition to damages caused by physical contact with trawl gear, trawling can have an indirect impact on CWCs.…”
Section: Threats and Canyons As Refuges For Cwc Habitatsmentioning
confidence: 99%
“…Trawl gear can damage CWC communities by reducing or changing coral abundances, diversity and community or the removal of structuring species (reviewed by Clark et al, 2016), as shown for coral reefs of the NE Atlantic (Hall-Spencer et al, 2002) and Solenosmilia thickets on Australian seamounts (Althaus et al, 2009). In addition to damages caused by physical contact with trawl gear, trawling can have an indirect impact on CWCs.…”
Section: Threats and Canyons As Refuges For Cwc Habitatsmentioning
confidence: 99%
“…It is postulated that trawling practices may have stronger effects on the deep-sea mega-epibenthic fauna in comparison with shallower areas (Clark et al, 2015). This arises from the typical characteristics of deep-sea species, particular lifehistory traits (k-selected; e.g., slow growth, high longevity), metabolic rates (low productivity) and reproductive strategies (e.g., intermittent spawning events), which make them more vulnerable and less resilient to the effects of trawling practices (Thrush and Dayton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This arises from the typical characteristics of deep-sea species, particular lifehistory traits (k-selected; e.g., slow growth, high longevity), metabolic rates (low productivity) and reproductive strategies (e.g., intermittent spawning events), which make them more vulnerable and less resilient to the effects of trawling practices (Thrush and Dayton, 2002). Heavier trawl gears and more localized practices can also exert a stronger pressure on deepsea habitats (Clark et al, 2015). Yet, the effects on deepsea benthic habitats and mega-epibenthic assemblages are still debated and geographically dependent, since in most cases we lack either background knowledge of the biodiversity on the long-term targeted areas, or an obligatory legislation that requires impact assessment and monitoring programmes at recent fishing grounds (Clark et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations